Effectiveness of composite jacket strengthening of reinforced concrete columns under eccentric load after fire exposure - Mohammed Salah Dimia; Ahmed Rafik Belakhdar; Rachid Rabehi; Mohamed Baghdadi; Antonio Marcos de Oliveira Siqueira; Julio Cesar Costa Campos (The Journal of Engineering and Exact Sciences)
This research presents a numerical study of the behavior of reinforced columns with a square cross section subjected to eccentric stress under the influence of fire. As a first step, the study examined the effects of exposing columns to fire with an increasing temperature up to 600°C for 60 minutes under eccentric loading conditions (e/b = 0, 0.1, 0.15, 0.20). As a second step, the columns were strengthened with a 100-mm concrete jacket and shirts supported by a steel structure consisting of vertical angles and horizontal spreaders to determine the effectiveness of the strengthening in increasing the resistance of these damaged columns. After the fire, this type of reinforcement is considered better than reinforcement with concrete shirts, reinforcement with carbon fiber-reinforced polymers, and others because of its advantages. There are many advantages to the ease and speed of implementation. The results showed that the columns that were repaired and strengthened after the fire with the steel structure casing led to a significant increase in resistance. It was found that the greater the thickness of the steel structure, the greater the resistance, and that the greater the eccentricity ratio, the lower the resistance as well as the collapse load.